(untitled) (Quest Journal of Management and Social Sciences, 2023)
Background: The study intended to examine the factors affecting the share price of Nepalese commercial banks. Market price per share is selected as the dependent variable, while earning per share, price-earnings ratio, book value per share, return on assets, and size was chosen as firm-specific independent variables, while inflation, broad money supply and gross domestic product (real) were taken as external factors. In order to fulfil these objectives, the data were collected from the banking and financial statistics and annual report published by Nepal Rastra Bank and the annual report of selected banks which is based on panel data over 11 years of the period from 2012 to 2022 of selected 13 out of 21 commercial banks of Nepal. The Descriptive and casual relationship research design has been used using secondary data. The multiple regression models were estimated to test the impact of firm-specific factors on the share price of Nepalese joint venture commercial banks; results show that variables like earnings per share, price-earnings ratio, book value per share and return on assets are the major determining stock price having a significant impact on the price of share except for the size of the firm having an insignificant impact in the context of joint venture commercial banks of Nepal. Objective: The main purpose of the study is to examine the factors affecting the share price of commercial banks in Nepal, considering the internal and external factors like size, EPS, P/E Ratio, BVPS ROA, Inflation, broad money supply and gross domestic product on the stock price. Method: The pooled cross-sectional data analysis has been undertaken in the study. The research design adopted in this study is causal-comparative type as it deals with the relationship of firms’ specific and macroeconomic variables with market price per share. From the year 2012 to 2022, i.e. 11 years, samples are taken from 13 Commercial banks in Nepal. Findings: Regression analysis shows the relationship between the internal and external factors influencing the share price of listed commercial banks of Nepal. Implication: The result of this study suggests investors should pay attention to BVPS, P/E ratio, ROA and Inflation before making any decisions regarding the investment in stock of commercial banks. The results of this study uncovered new evidence from the Nepalese perspective, which is considered to be valuable to the market participants. Thus, the findings of this study seem to be particularly useful for equity investors and fund managers as they can watch out for these significant factors while estimating stock returns and predicting share prices.